Fineapple Harvesting Co.: A feasibility study on pineapple cultivation - Abadicio, Charles Darwin M.; Barican, Daryl Joy E.; Canaria, Leemwell U.; Cardino, Lhoel Jay P.; Cimatu, Louris Jen M.; Dela Paz, Aliya Monica G.; Velarde, Javin S. 4 0 16; 5
PROJECT STUDY: Name of the Firm: The business name is Fineapple Harvesting Co. Fineapple is acombined word between two words which are Fine and Pineapple the start-up business aims to cultivate Pineapples. Pineapples are not hard to grow here in the Philippines since it is a tropical country. The company aims to produce high-grade Pineapples that will be good for consumption hence the name, Fineapple. The business, also centered around agriculture and agribusiness, is connected to the second part of the name, Harvesting. The location of the business is at Brgy. Halyhayin, Pililla, Rizal.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2